Análise de métodos de hidrógrafa unitária - Mendonça, Antonio Sergio Ferreira (1977)
Detailed analysis of the main methods of calculus for the unit hydrograph, which are: the methodologies of Sherman, S-Curve, Snyder, Commd Soil Conservation Service, Clark, Nash, O'Donnell and Inversion via Matrices. There were developed computational programs for all methods, in Fortran Language. The machine used was a Burroughs 6700 pertaining to the Nucleo de Computação Eletrônica da UFRJ. Applications were made with data obtained from stations situated in the hydrographic basin of Rio Acari in Rio de Janeiro, Brazil. Furthermore, conparisons were made among the methods based upon the results obtained from the applications mentioned above, as well as in the analysed literature.